2015
DOI: 10.1007/s11084-015-9458-x
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized Martian-Like Pure CO2 Atmosphere Supports Strong Growth of Cyanobacteria, and Causes Significant Changes in their Metabolism

Abstract: Surviving of crews during future missions to Mars will depend on reliable and adequate supplies of essential life support materials, i.e. oxygen, food, clean water, and fuel. The most economical and sustainable (and in long term, the only viable) way to provide these supplies on Martian bases is via bio-regenerative systems, by using local resources to drive oxygenic photosynthesis. Selected cyanobacteria, grown in adequately protective containment could serve as pioneer species to produce life sustaining subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 36 publications
(54 reference statements)
0
31
0
Order By: Relevance
“…Atmospheric N 2 transformed to organic N through biological fixation by cyanobacteria has δ 15 N values close to zero (Aranibar et al, 2004;Nadelhoffer and Fry, 1994). Across 7 months of active N fixation, isotopic N values averaged 0.9 ‰, indicating cyanobacteria were likely the primary source of bioavailable N (Evans and Ehleringer, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atmospheric N 2 transformed to organic N through biological fixation by cyanobacteria has δ 15 N values close to zero (Aranibar et al, 2004;Nadelhoffer and Fry, 1994). Across 7 months of active N fixation, isotopic N values averaged 0.9 ‰, indicating cyanobacteria were likely the primary source of bioavailable N (Evans and Ehleringer, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that N enrichment was associated with Gloeocapsa (Wyatt and Silvey, 1969), Porphyrosiphon (Prasanna et al, 2000) and Schizothrix (Berrendero et al, 2016). Indeed, many cyanobacteria obtain N by scavenging from mutually shared EPS (Rossi et al, 2017) or have multiple mechanisms for N fixation either in the dark (Lüttge, 1997), through O 2 inhibition (Stal, 1995), in anaerobic circumstances (Murukesan et al, 2016) or aquatic cyanobacterial mats when submerged under water (Berrendero et al, 2016;Stewart, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Mars Direct plan (Baker & Zubrin 1990;Zubrin et al 1991;Zubrin & Wagner 2011) ) under a 99% argon (Ar), 1% CO 2 atmosphere . Recently, levels of about 25 µmol mg Chl a −1 h −1 were also reached with A. cylindrica cultures under high CO 2 /low N conditions (Murukesan et al 2015). With a concentration of 50 mg Chl a ml…”
Section: Producing Biofuelsmentioning
confidence: 95%
“…5). Later results showed that an increase in CO 2 concentration (at least up to 20%, even though growth rates started to decrease after 10% for the 1-bar samples) under either 1 bar or 100 hPa leads to higher growth rates than ambient air composition at the corresponding pressure (Murukesan et al 2015;unpublished data). Thus, this strain seems to benefit from higher-than-usual pCO 2 , with a saturation about 4 hPa, at which level an around 3.5-fold increase in growth rates is observed for cells previously grown in ambient terrestrial atmosphere.…”
Section: Atmospheric Pressure and Compositionmentioning
confidence: 98%